The Effect of Using SQ3R Strategies Toward Students Reading Comprehension in Narrative Text at The Tenth Grade of SMAN 1 Cihara in Academic Year 2021/2022 - Sarni, Sarni; Novari, Ari Fajria; Riandi, Riandi (Journal of English Education Studies, 2023)
The objective of this research is to obtain empirical evidence about the effect of SQ3R technique in the students’ reading comprehension of narrative text. The method used in this research was quantitative method and the research design was quasi-experimental. The samples of this study were 70 students of the tenth grade of SMAN 1 Cihara in the Academic year 2022. There are two classes of this research, namely X3 as the experimental class and XI as the control class. Each class consisted of 35 students. The experimental class was taught by using SQ3R strategies, while the control class was taught by using skimming strategies. The result of this research showed that there was effect of SQ3R strategies towards students’ reading comprehension in narrative text. The finding was supported by the result of the hypothesis testing by using paired sample t-test in SPSS 22 for windows showed the value of t calculation > t-table 11.756 in experimental class. The significance value is less than 0.05 (p=0.00< 0.05 in experimental class). It was concluded that the alternative hypothesis (Ho) was accepted. Therefore, the researcher concludes that there is a significant effect of SQ3R strategies on reading comprehension.